Penerapan Asas Kepentingan Terbaik Bagi Anak berdasarkan Perpektif Undang-Undang Sistem Peradilan Pidana Anak - Istriani Istriani; Laila Marotus Khoiriyah (Neolectura, 2022)
Children's rights must be upheld and implemented in all nations that have established conventions on the rights of the child. This includes taking all necessary legislative and other measures. This is because only a child can determine whether a decision or policy will be applied to him or her, it must be prioritized for the best interests of the child, one of which is by implementing the settlement of a child's case in conflict with the law, a child should not be convicted, but they must given protection and assistance. The purpose of this study is to find out how the principle of the best interests of children is regulated in the SPPA Law. The method used is normative juridical. The study found that cases involving children must be resolved according to the juvenile criminal justice system through diversion which must be pursued at every stage of the criminal justice system. This is important for the fulfillment of the child's future and the opportunity to become a productive and responsible individual. Children need to be protected through the principle of the best interests of the child. According to the principle of the best interests of the child, all decisions regarding the child, including those made by parents, society and the government, must be made with the best interests of the child in mind.